Comparative photo-degradative treatment of dyeing industry wastewater containing diazo dye by UV/Peroxydate and UV/Persulfate − oxidation processes. Issue 4 (5th September 2022) - Laftani, Yasmine; Chatib, Baylassane; Boussaoud, Abdelghani; Hachkar, Mohsine; El Makhfouk, Mohammed
Abstract: Generation of anion sulfate radicals (SO4 − ) and hydroxyl radicals (HO ) by UV/Persulfate and the UV/Peroxydate processes have been successfully studied to degrade Ponceau S dye. Under [PS] = 0.06 mM; [H2 O2 ] = 2 mM; [S2 O8 2- ] = 2 mM, the UV/Persulfate process was effective ( k app = 0.163 min −1 ) than the UV/Peroxydate process ( k app = 0.054 min −1 ). The lack of dissolved oxygen, the excess of hydrogen peroxide (H2 O2 ) dosage at 2 mM, and the alkaline pH of 10.01 significantly reduced the UV/Peroxydate efficiency. The scavenging effect of the hydrogenocarbonates and nitrates on the PS dye degradation by the UV/Persulfate process was significant, whereas chlorides had a slight influence. The composition of seawater in chlorides, sulfates, carbonates, and bromides decreased the photoactivity of the studied processes. The presence of phenol showed that the reactive affinity of the (HO ) is more superior to the SO4 − . The UV/Persulfate process achieved 82.35% of chemical oxygen demand removal against 59.56% for the UV/Peroxydate in about 100 min. This study demonstrated that the UV/Persulfate process is a viable option for PS dye degradation. To the best of our knowledge, this is the first report for studying the PS dye degradation under varying some new operational factors. However, the identification of by-products, their nature, and their concentration requires special attention. HIGHLIGHTS: Higher degradation of Ponceau S dye was obtained with the UV/ process against the UV/H2 O2 process. Active species such as and play key roles in the degradation of Ponceau S dye. The seawater matrix promoted the scavenging reactivity of the active radicals. The introduction of anions reduced the oxidation by the UV/ process. The UV/ process achieved a higher chemical oxygen demand removal. Graphical Abstract